2013
DOI: 10.3892/etm.2013.1372
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin in the therapy of adult acute fulminant myocarditis: A retrospective study

Abstract: Acute fulminant myocarditis (AFM) is a serious heart disease with limited treatment. This observational retrospective study aimed to investigate whether intravenous immunoglobulin (IVIG) was able to improve left ventricular function and reduce the episodes of arrhythmia in adult patients with AFM. The medical records of all patients with AFM who were admitted to the Critical Care Unit of Guangdong General Hospital (Guangzhou, China) between January 2001 and December 2010 were reviewed. A cohort of 58 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 33 publications
(38 reference statements)
0
13
0
3
Order By: Relevance
“…A retrospective study of 58 fulminant myocarditis patients in Guangdong province of China revealed that compared with patients who did not receive IVIG, patients treated with 400 mg kg -1 IVIG had a remarkable improvement in LVEF and LVEDD after 4 weeks (P=0.011 and 0.048, respectively). In addition, the incidence rate of ventricular tachycardia or fibrillation decreased significantly in the treatment group (P=0.025), and there was a clear tendency toward decreased mortality that did not reach statistical significance (6% vs. 27%, P=0.072) (Yu et al, 2014). Treatment with IVIG should be administered in sufficient doses as early as possible.…”
Section: Ivigmentioning
confidence: 93%
“…A retrospective study of 58 fulminant myocarditis patients in Guangdong province of China revealed that compared with patients who did not receive IVIG, patients treated with 400 mg kg -1 IVIG had a remarkable improvement in LVEF and LVEDD after 4 weeks (P=0.011 and 0.048, respectively). In addition, the incidence rate of ventricular tachycardia or fibrillation decreased significantly in the treatment group (P=0.025), and there was a clear tendency toward decreased mortality that did not reach statistical significance (6% vs. 27%, P=0.072) (Yu et al, 2014). Treatment with IVIG should be administered in sufficient doses as early as possible.…”
Section: Ivigmentioning
confidence: 93%
“…A retrospective study indicated that applying IVIG to AFM patients may improve left ventricular function and reduce the incidence of fulminant arrhythmias. 7) Nevertheless, another two randomized controlled trials (RCTs) in pediatric or adult patients reported inconsistent results. 8,9) In those studies, no remarkable difference in survival rate was found, and there was no rigorous evidence indicating whether IVIG could amplify the improvement in left ventricular function.…”
mentioning
confidence: 99%
“…Of note, a total of 27 patients that did not receive immunosuppressive treatment were included in two of those studies. 53,56 Seven patients died in this control group, suggesting a mortality rate of 26%. Various immunosuppressive regimens were studied in the last decades, and their role in recent-onset idiopathic or inflammatory cardiomyopathy remains highly controversial.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 79%